2008
DOI: 10.1016/j.envint.2008.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of organochlorine pesticides – lindane, p,p′-DDT, and heptachlor epoxide – in surface water of China

Abstract: Persistent organochlorine pesticides pollutants (OCPs) have been reported to occur at relatively high concentrations in some Chinese waters. In order to map the distribution of organochlorine pesticides in the surface water throughout China, samples were collected from over 600 sites in seven major river basins and three main internal rivers drainage areas during 2003 and 2004. The surface water samples were analyzed for the representative organochlorine pesticides contaminants including lindane (gamma-HCH), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 36 publications
1
36
0
2
Order By: Relevance
“…Longerchained PFCAs (C N 8) were not detected in most of the surface water samples. Gao et al (2008) reported a high detection frequency for PFDA and PFUnDA in sediment and attributed the degradation of precursors as the cause. In the surface waters, PFDA and PFUnDA concentrations were below the detection limit (0.02 ng/L).…”
Section: Ionic Pfass In Surface Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Longerchained PFCAs (C N 8) were not detected in most of the surface water samples. Gao et al (2008) reported a high detection frequency for PFDA and PFUnDA in sediment and attributed the degradation of precursors as the cause. In the surface waters, PFDA and PFUnDA concentrations were below the detection limit (0.02 ng/L).…”
Section: Ionic Pfass In Surface Watermentioning
confidence: 99%
“…The western part (W63 and W64, 52-60 ng/L) of the Laizhou Bay mouth exhibited lower ∑PFAS concentrations than the eastern part (W65-66, 108-118 ng/L). The western part is mainly influenced by the Yellow River, which recently suffered from decreasing water discharge and serious pollution (Gao et al, 2008;He et al, 2006). The eastern part is the gateway through which coastal water and adjacent river water move out of the Laizhou Bay.…”
Section: Distribution and Transportation Of Ionic Pfass In Surface Watermentioning
confidence: 99%
“…A survey during 2003-2004 of 217 reservoirs and 406 rivers and lakes in seven major river basins revealed that surface waters in China also suffered from moderate pollution by OCPs (Gao et al 2008). Lindane (c-HCH) and p,p 0 -DDT were detected in 84 and 63% of sites, with a mean concentration of 0.0313 lg L -1 (ND *0.860 lg L -1 ) and 14.6 lg L -1 (ND *0.368 lg L -1 ), respectively.…”
Section: Pollution From Pesticidesmentioning
confidence: 99%
“…[27] It was found in drinking water, groundwater, river, and land runoff at seven locations in the USA and Europe at nanolevels. [28] Recently, this compound was detected in Chinese surface water samples [29] and rivers in Vietnam. [30] DDT has been always defined as the most abundant group among OCP due to its long-time usage and high persistency.…”
Section: Resultsmentioning
confidence: 99%